Tongue pyogenic granuloma excision by using ultrasonic scissors - Mohamad, Irfan; Periasamy, Chentilnathan; F. Hussein Al-Hadeethi, Yahia (Universiti Sains Malaysia ( USM), 2011)
Pyogenic granuloma is a benign lesion which is commonly found in the oral cavity. It is a reactive inflammatory process of the injured mucosa to trauma. It can appear as a sessile or pedunculated mass with smooth or lobulated surface, which sometimes can mimic malignant lesion. Excision biopsy of the lesion is the confirmatory investigation which also a treatment tool. We report a case of middle-aged lady who had pyogenic granuloma of the tongue, which was safely excised using ultrasonic scissors. This case highlights the new technique of using ultrasonic instruments for excision of benign tongue lesion, with marked reduction of blood loss and operation time.